INFLUENCES OF INDIUM TIN OXIDE LAYER ON THE PROPERTIES OF RF MAGNETRON-SPUTTERED (BASR)TIO3 THIN-FILMS ON INDIUM TIN OXIDE-COATED GLASS SUBSTRATE - KIM, TS; OH, MH; KIM, CH (JAPAN J APPLIED PHYSICS, 1993)
Nearly stoichiometric ((Ba+Sr)/Ti=1.08-1.09) and optically transparent (BaSr)TiO3 thin films were deposited on an indium tin oxide (ITO)-coated glass substrate by means of rf magnetron sputtering for their application to the insulating layer of an electroluminescent flat panel display. The influence of the ITO layer on the properties of (BaSr)TiO3 thin films deposited on the ITO-coated substrate was investigated. The ITO layer did not affect the crystallographic orientation of (BaSr)TiO3 thin film, but enhanced the grain growth. Another effect of the ITO layer on (BaSr)TiO3 thin films was the interdiffusion phenomenon, which was studied by means of secondary ion mass spectrometry (SIMS). As the substrate temperature increased, interdiffusion intensified at the interface not only between the grown film and ITO layer but also between the ITO layer and base glass substrate. The refractive index (n(f)) of (BaSr)TiO3 thin film deposited on a bare glass substrate was 2.138-2.286, as a function of substrate temperature.
Keywords: BATIO3; SILICON